The Legal Concepts of Online Commerce - Kotkowski, Jakub (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2018)
The aim of the study is to present the selected legal concepts of online commerce. Elec-tronic commerce is still a relatively young, and thus only emerging, field of legal and economic marketing. Nevertheless, it exerts a serious and enormous influence on the entirety of social, economic and legal relations on a global scale. Bearing in mind this as-sumption the author pays attention to the selected topics of online commerce that leads to a conclusion that the existing legal and jurisprudential traditions are able to adapt to new, specific challenges posed by the development of technological civilization.